2016
DOI: 10.1148/radiol.2015142856
|View full text |Cite
|
Sign up to set email alerts
|

Computer-extracted Features Can Distinguish Noncancerous Confounding Disease from Prostatic Adenocarcinoma at Multiparametric MR Imaging

Abstract: The best features with which to discriminate prostate cancer from noncancerous benign disease depend on the type of benign disease and cancer grade. Use of the best features may result in better diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…(48,49) where a new classifier was introduced to separate prostate cancer and benign confounders on MRI. The pathology annotations were propagated to MR images by registration of whole-mount slides and manual annotation of cancer, benign prostatic hyperplasia (BPH), prostatic intraepithelial neoplasia (PIN), inflammation.…”
Section: Review Of Applications Of Radiomics To Prostate Cancermentioning
confidence: 99%
“…(48,49) where a new classifier was introduced to separate prostate cancer and benign confounders on MRI. The pathology annotations were propagated to MR images by registration of whole-mount slides and manual annotation of cancer, benign prostatic hyperplasia (BPH), prostatic intraepithelial neoplasia (PIN), inflammation.…”
Section: Review Of Applications Of Radiomics To Prostate Cancermentioning
confidence: 99%
“…Nonetheless, inter-observer variability in interpreting prostate mpMRI and existence of benign confounders on imaging [12, 13] still limit accurate detection and diagnosis of CaP. Recent studies [11, 1416] have shown radiomics based classifiers can improve the accuracy and reproducibility in localizing prostate cancer lesions on mpMRI (which includes T2w, diffusion weighted (DWI) and dynamic contrast enhanced (DCE)).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that intravoxel incoherent motion (IVIM) parameters (the pure diffusion coefficient D t , the pseudo-diffusion fraction F p and the pseudo-diffusion coefficient D p ) derived from a biexponential fit to DW-MRI [14,15] correlate with the cancer's aggressiveness [16]. In addition, parameters derived from high b value DW-MRI (as acquired or following Hessian focality filtering [17]) were found to be useful to distinguish noncancerous disease from prostatic adenocarcinoma [18]. Although all previous studies showed promising results, the association between lesion aggressiveness and values of DW-MRI parameters is not sufficiently specific to allow application to individual patients.…”
Section: Introductionmentioning
confidence: 99%